Analisis Harga Pokok Produksi pada Belt Conveyor dan Roller Conveyor dengan Metode Job Order Costing pada PT. XYZ - Nur Laili Rahmawati; Yoniv Erdhianto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
In global competition, companies must be able to set competitive selling prices. Production cost components such as raw material costs, direct labor costs, and factory overhead costs are all included in the cost of goods manufactured. This study analyzes the COGS with Job Order Costing at PT. XYZ, a make-to-order company. The study was conducted by comparing COGS with Job Order Costing between Box Roller Conveyor and Bag Stop & Go Belt Conveyor as well as material usage and outsourcing. The results of the study indicate that Job Order Costing at PT.XYZ accurately traces the contribution of material costs and outsourcing to total production costs, and evaluates efficiency and cost control on each project with different characteristics. The use of Job Order Costing shows that Bag Stop & Go Belt Conveyor has a higher COGS of Rp299,655,813 than the COGS of Box Roller Conveyor of only Rp209,740,142. The cost structure shows that outsourcing is the most dominant component, reaching more than 98% of HPP on Bag Stop & Go Belt Conveyor, while raw material costs contribute less than 3%, so it can be concluded that the outsourcing vendor management strategy greatly affects the efficiency of production costs at PT. XYZ.